Decolonising the ESL/EFL Classroom: Textbook Content, National Identity, and the Malaysia Madani - Hazleena Baharun; Habibah Ismail; Haliza Harun; Norhaili Massari (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia